Finlandia Tero Saarinen & Company Toothpick - Hutera, Donald (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Tero Saarinen premieres in London and Venice. PALABRAS CLAVE: Tero Saarinen, Company Toothpick, Japanese butoh dance, Petrushka, Kaze.